Улс төрийн намын системийн судалгаа, ангилал - С.Мөнхбат; Э.Бат-Эрдэнэ (Politology, 2024)
A party system is a concept in comparative political science concerning the system of government by political parties in a democratic country. The idea is that political parties have basic similarities: they control the government, have a stable base of mass popular support, and create internal mechanisms for controlling funding, information and nominations. This article contributes to the study conception and classification of party system by political scientists and scholars. The concept was originated by European scholars studying the United States, especially James Bryce and Moisey Ostrogorsky, and has been expanded to cover other democracies. Giovanni Sartori devised the most widely used classification method for party systems. The party system in Mongolia has been characterized by instability and fragmentation since the democracy in 1990. In part this instability is rooted in the legal framework regulating political parties as organizations and the factions that parties performs in a democracy. The article outlines the formation and development that analyzed political party system in Mongolia since 1990.